Extracellular vesicle therapy for non-ischemic heart failure: A systematic review of preclinical studies - Ramana Vaka; Sophie Van Remortel; Valentina Ly; Darryl R. Davis (Extracellular Vesicle)
Cell-derived extracellular vesicles (EVs) are being actively explored as a novel acellular approach to heart failure. Accumulating evidence suggests EVs improve cardiac function in non-ischemic heart failure, but the strength and consistency of this effect is unknown. As such, we critically appraised the preclinical literature supporting the ability of EVs to improve cardiac function in animal models of non-ischemic heart failure. After a systematic search that yielded 18 studies, we determined the overall effect of EV treatment on left ventricular function and performed regression analysis to identify EV effects on clinically relevant parameters. EV treatment uniformly improved ejection fraction (2.41 [95% CI: 1.76, 3.06; p < 0.00001; I2 = 46%]) and fractional shortening (2.22 [95% CI: 1.40, 3.05; p < 0.00001; I2 = 56%]) as compared to untreated control animals. Secondary outcomes (such as left ventricular volumes or myocardial fibrosis) were similarly improved in EV treated animals. Although the number of studies included in the analysis was modest, there was no evidence for a publication bias. In conclusion, EV treatment improves cardiac function in preclinical models of non-ischemic heart failure. Although EVs originated from dissimilar cell lines and were applied to a variety of different animal models, we observed a consistent improvement in cardiac function suggesting application of EVs to non-ischemic heart failure has merit and warrants future attention.